Interior Environment Enhancing Physical Treatment: A Case of Child Autistic Medical Development - Nipattha Noiprawat; Nopadon Sahachaisaeree (My University, 2012)
Interior environment has been a crucial factor determining the effectiveness of medical treatment. The settings should support their unique learning abilities and be able to attract their attention. The study uses the autistic treatment environment as a case study to examine relevant environmental factors supporting the learning process. Data collection comprises with questionnaire survey, behavioral observation within diverse environmental and observation checklist during treatment activities. The final environment modeling could be applied as a part of special educational programs extenuated the behavioral and emotional disorders, and to improve the social skill.
Keywords: Learning environment; Child Therapy and Development